Crosstalk In Mechanomyographic Signals From Elbow Flexor Muscles During Submaximal To Maximal Isometric Flexion, Pronation, And Supination Torque Tasks - Sundaraj, Kenneth; Talib, Irsa; Lam, Chee Kiang (American Society of Mechanical Engineers (ASME), 2021)
This study analyzed the crosstalk in mechanomyographic (MMG) signals from elbow flexors during isometric muscle actions from 20% to 100% maximum voluntary isometric contraction (MVIC). Twenty-five young, healthy, male participants performed the isometric elbow flexion, forearm pronation, and supination tasks at an elbow joint angle of 90 deg. The MMG signals from the biceps brachii (BB), brachialis (BRA), and brachioradialis (BRD) muscles were recorded using accelerometers. The cross-correlation coefficient was used to quantify the crosstalk in MMG signals, recorded in a direction transverse to muscle fiber axis, among the muscle pairs (P1: BB and BRA, P2: BRA and BRD, and P3: BB and BRD). In addition, the MMG RMS and MPF were quantified. The mean normalized RMS and mean MPF exhibited increasing (r > 0.900) and decreasing (r < 0.900) trends, respectively, with increases in the effort levels in all three tasks. The magnitude of crosstalk ranged from 0.915% to 21.565% in all three muscle pairs. The crosstalk was found to exhibit high positive correlations with submaximal to maximal flexion [P1 (r ¼ 0.970), P2 (r ¼ 0.951), and P3 (r ¼ 0.824)], pronation [P1 (r ¼ 0.811), P2 (r ¼ 0.763), and P3 (r ¼ 0.901)] and supination [P1 (r ¼ 0.898), P2 (r ¼ 0.838), and P3 (r ¼ 0.852)] torque levels (eight out of nine p-values were < 0.05). Regardless of the high positive correlation between crosstalk and level of effort, the crosstalk remained at a low range (0.915–21.565%) with increases in the torque levels